2023
DOI: 10.1155/2023/9905842
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Dockless Shared E-Scooter Demand by Time of Day: A Case Study of Austin

Abstract: The goal of the current study is to identify and quantify the influence of various contributing factors on dockless e-scooter demand. Drawing on high-resolution e-scooter trip level data for 2019 from Austin, Texas, we develop census tract (CT) level demand data for four time periods of the day. The time-period specific data is partitioned for weekdays and weekends. Using the prepared datasets, we develop a joint panel linear regression (JPLR) model framework that accommodates for the influence of unobserved f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Previous research on shared e-scooter use identified several factors that increase e-scooter demand, including the presence of businesses and industries, transit accessibility, mix of land uses, locations in central business districts, population density, bike scores, student-populated areas, and weather conditions-increased e-scooter demand [3,43,[69][70][71].…”
Section: Demand Prediction Studies Of E-scootersmentioning
confidence: 99%
“…Previous research on shared e-scooter use identified several factors that increase e-scooter demand, including the presence of businesses and industries, transit accessibility, mix of land uses, locations in central business districts, population density, bike scores, student-populated areas, and weather conditions-increased e-scooter demand [3,43,[69][70][71].…”
Section: Demand Prediction Studies Of E-scootersmentioning
confidence: 99%